Acquired oculomotor muscle fibrosis in infant: case report - Souza-Dias,Carlos Ramos de (2011)
The authors report the case of a 5 year-old boy who up to 2 years old presented normal eyes, when his right eye started to deviate upward and laterally, until be hidden under the superior lid. At the surgery, a strong passive limitation to infraduction of this eye was felt. He had already been operated on in another clinic, but the surgeon could not succeed in hooking his superior rectus. With great difficulty, the only thing that we could do was a free tenotomy of the superior rectus. As the eye was equilibrated in a moderate abduction, we performed an 8 mm recession of the lateral rectus. As there was still a small hypertropia and exotropia postoperatively, we performed in a second operation an eight millimeters resection of the medial rectus, a recession with anterior transposition of the inferior oblique and an advancement of the inferior rectus according to the Romero-Apis technique, in order to avert circulatory problems to the anterior segment of the eye. As he presented a small blepharoptosis, we did, in a third surgery, a tarsectomy according to the Fasanella-Servat technique, with good result. He ended with good eye position, almost no limitation of the horizontal movements and - 3 limitation of up and down ductions. The magnetic resonance imaging showed an altered image of the superior rectus, suggesting fibrosis post myositis.